Radiation response of multicomponent L12 γ′ precipitates strengthened high entropy alloys: The role of γ/γ′ interface - Shasha Huang; Haijun Fu; Yaoxu Xiong; Wenyu Lu; Shihua Ma; Xuepeng Xiang; Ji-Jung Kai; Shijun Zhao (Journal of Materials Research and Technology)
The advancement of high entropy alloys (HEAs) has stimulated the development of multicomponent L12 γ′ intermetallics, which exhibit both excellent strength and ductility. These intermetallics with long-range order are typically employed as coherent precipitates to enhance the high-temperature performance of HEAs. This study investigates the influence of multicomponent γ′ intermetallics on the irradiation response of the strengthened HEA γ phase, focusing on the role of the multicomponent γ/γ′ interface in defect production and evolution. Our results indicate that the chemical disorder within the multicomponent γ′ phase leads to a broad defect energy spectrum near the interface zone, diminishing its effectiveness as a defect sink. Based on these observations, we propose that, distinct from traditional superalloys, the γ/γ′ interface plays a minor role in the irradiation resilience of multicomponent γ′ intermetallics-strengthened HEAs. Instead, the inherent chemical disorder within the multicomponent γ′ intermetallics emerges as the key factor.